Influence of Polymorphism on Glycosylation of Serum Amyloid A4 Protein - Toshiyuki Yamada; Jyunji Sato; Kazuhiko Kotani; Masafumi Tanaka (Biochemistry Research International)
Serum amyloid A4 (SAA4) is a constitutive apolipoprotein of high-density lipoprotein. It exhibits N-linked glycosylation in its second half. There are both glycosylated and nonglycosylated forms in plasma and the ratio of these two forms varies among individuals. This study was conducted to examine the influence of genetic polymorphism of SAA4 on its glycosylation status. In 55 healthy subjects, SAA4 polymorphism was analyzed by PCR combined direct sequencing and its glycosylation status was analyzed by immunoblotting. The results showed that the percentage of glycosylation in subjects with amino acid substitutions at positions 71 and/or 84 was significantly (P<0.05) higher than that in subjects with the wild type. The polymorphism had no influence on the plasma concentration of SAA4. These findings suggest that the changes in protein structures alter the efficiency of glycosylation in the SAA4 molecule. The functional implication of this should be of interest.